Awareness about disaster management among accredited social health activists in field practice area of a medical college in Mysuru - Thomas, Jose Jom; H., Chandana; Kulkarni, Praveen; B., Prakash; M. R., Narayana Murthy (International Journal Of Community Medicine And Public Health, 2019)
Background: The changing global climate due to human influences is leading to a greater incidence of extreme weather events and natural disasters. The natural and man-made disasters have a great impact on physical and mental health and health system. Disaster preparedness is therefore important at all levels of the health system. Being the first contact of the health system to the communities, accredited social health workers have a great role in managing the disasters at the village level. This study attempts to assess the awareness regarding disaster management among accredited social health activists (ASHAs) in the field practice area of J.S.S. Medical College in Mysuru, Karnataka. Methods: A community-based cross-sectional study was conducted for one month in July 2019. A total of 40 ASHAs were assessed by direct interview method using a pre-structured, validated questionnaire. The data were entered into the Microsoft Excel spreadsheet and analyzed using SPPS version 22. Results: The median years of experience of ASHAs were 10 years (interquartile range: 5.75-10) with a minimum and maximum experience of 2 and 10 years respectively. None of the study participants had received any trainings or mock drills for disaster management/ preparedness. The awareness about disaster management was low among the ASHAs assessed. Most of the ASHAs (92.5%) had average knowledge about disaster management while 7.5% had only poor knowledge. Conclusions: The awareness about disaster management among ASHAs is very poor. We recommend training programs and mock drills for the frontline health workers to improve awareness and disaster preparedness.